Effect of natural variations with respect of time interval in handwritings of individuals - Gupta, Shruti; Garg, Rakesh K.; Nath, Surinder (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
In the present investigation an attempt has been made to extract out natural variations with time interval, a total of 540 60 samples from each age group — 30 samples each from males & females collected from 9 different age groups, that is two handwriting samples in present handwriting with an interval of 5–10 minutes between the two handwritings with content same as that of previous written script old handwriting which is also taken as a sample for comparative study with time interval ranged from 2–33 years between present and old handwriting. It has been found that connectivity between letters, alignment and spacing are highly significant characteristic along with those which remain unaffected and intact by showing consistency in skill and speed in due course or age and time. The findings of the present study will assist in the cases which are lacking in contemporary handwritings and can be undertaken with ease by taking into account the handwriting characteristics which are prone to variations.
Keywords: zapis asynchroniczny; naturalne różnice; przedział czasowy; współczesność; spójność